Atherogenicity of Diabetic Rats Administered Single and Combinatorial Herbal Extracts - Abdullah Ahmad Bilgasem Algarni; Yasser Salem Rajah Albaledi; Khaled Msfer M Algamdi; Adel Mutair Musne Alsulami; Zaid Azzam Al Sulami; Mohamed Bashah Alsuhaymi; Ahmed Saud Samran Althagafi; Abdulaziz Yahya Baroji Al-Zubaidi; Abdulrahman Fawaz Nasser Alghamdi; Ayat Essam Shaaban (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Diabetes mellitus (DM) is an endocrine condition largely defined as inadequate action or secretion of endogenous insulin, resulting in chronic metabolic syndromes. Aim: To evaluate atherogenicity of diabetic mice after administration of combinatorial and single herbal extracts. Materials and methods: The search has been conducted in the following databases: Web of Science, MEDLINE (PubMed), & the Cochrane Library. The trial quality has been assessed utilizing the Cochrane Risk of Bias evaluation instrument one (ROB 1), which is specifically tailored for interventional trials. This evaluation tool includes various factors, including performance bias, selection bias, attrition bias, reporting bias, detection bias, & possible sources of bias. Each experiment has been examined for bias, with researchers classifying the degree of bias as "high," "low," or "unclear" for each evaluated parameter. Main finding: The linear regression study of the atherogenic index of plasma (AIP) against serum levels of LDL-C in the experimental mice groups yielded a closely fitted regression line (R² = 0.8275). The atherogenic protection in herbal extract-managed diabetic rats groups ranged from 33.4 to 81.7 percent. Conclusion: We determined that herbal extracts markedly decreased TG, TC, VLDL-C, & LDL-C levels, while elevating HDL-C as well as enhancing atherogenic risk indices, suggesting their potential as a therapeutic agent for diabetes treatment.